Aktueller Antisemitismus: ein Phänomen der Mitte? - Schwarz-Friesel, Monika (de Gruyter, 2010)
Anti-Jewish sentiment and prejudice are not a fringe-group phenomenon. In recent years the inhibition threshold for expressing anti-Semitic content in public has become lower, with Israel often serving as a screen for projecting anti-Jewish sentiment. This anti-Semitism of the mainstream of society was the focus of an interdisciplinary symposium in 2009 at Friedrich Schiller University Jena. The book contains the conference contributions, in which eminent experts on anti-Semitism such as Wolfgang Benz, Jehuda Reinharz and Martin Kloke analyse the phenomenon.